Testicular Toxicity Induced by Glyphosate (GLP) and Ameliorative Effect of Vitamin C in Wistar Rats - Namratha, M. Lakshmi; Lakshman, M.; Jeevanalatha, M.; Kumar, B. Anil (International Journal of Livestock Research, 2020)
The aim of the present experiment was to study the testicular toxicity induced by glyphosate and the protective role of Vitamin C in male albino Wistar rats. Forty eight (48) rats were randomized into four groups consisting of twelve (12) animals in each: Group 1 served as control, group 2 received glyphosate at a dose of 500 mg/kg b.wt, group 3 received Vitamin C at a dose of 250 mg/kg b.wt and group 4 received glyphosate (500 mg/kg b.wt) and Vitamin C (250 mg/kg b.wt). The treatment regimens were administered by oral gavage once daily for three weeks. The animals were sacrificed on 7th and 21st day post treatment. Results showed a significant increase in the percentage of abnormal sperms, reduction in the levels of testosterone and histopathological changes in the testes of glyphosate treated rats. However, administration of Vitamin C caused a mild to moderate ameliorative effect on the parameters investigated.